Evaluation of Impact of Prescribing Safety Assessment Workshop on Medical Doctors Using Kirkpatrick Model - Jehangir, Adnan; Danish, Khalid Farooq; Yasmeen, Rahila; Rabbani, Waqas; Ayub, Farhana (Journal of Rawalpindi Medical College, 2023)
Background Clinical pharmacology training is a prerequisite for all medical graduates. Prescription writing errors are not infrequent at primary health care level leading to threat to patient safety. Prescribers lacks uniform structured training and assessment which is one of the major factors for this situation across the country. In lots of institutions despite proper curriculum, learners lack interest because the subject importance is insignificant. Hence to bring more interest in pharmacology for prescribers there is a dire need for innovative and interesting methods of teaching and assessment, one of which is prescribing safety assessment (PSA). Objectives To assess if the PSA is superior method of training prescription writing than CPW To evaluate the workshop on prescription writing using guidelines of Kirkpatrick Model Methods It was an experimental study. 44 medical doctors participated; a pre-test was taken 01 week before the workshop. Afterwards, they were randomized into 02 groups, group A went through PSA and group B followed conventional prescription writing (CPW) 01-day workshop. At the end, post-test was taken from both groups. The qualitative data was also collected from participants on feedback proforma consisting of few closed ended questions on Likert scale. Results The independent t-test was used to compare the data as it was in normal distribution. Posttest performance of PSA group significantly increased P ˂ 0.001 as compared to CPW. Reaction to closed ended 13 questions on Likert scale showed high satisfaction from 4.32 to 4.84 on 5 points Likert scale on workshop satisfaction. Conclusion PSA is an effective teaching and assessment strategy for learning clinical pharmacology. The study objectively proves its effectiveness in comparison to CPW and provides a guideline to implement this innovative and useful tool for teaching and assessment. Keywords Prescribing safety assessment, conventional prescription writing, Faculty development, Workshop, Impact, Kirkpatrick model.